Facile and Novel Strategy for Methods of Extraction of Biofuel Grade Lipids from Microalgae- an Experimental Report - Baldev, Edachery; MubarakAli, Davoodbasha; Dhivya, Masilamani; Kanimozhi, Mahalingam; Shakena-Fathima, Thajuddin; Alharbi, Naiyf S.; Arunachalam, Chinnathambi; Alharbi, Sulaiman Ali; Thajuddin, Nooruddin (International Journal of Biotechnology for Wellness Industries, 2015)
The structural features of microalgal cell make it too difficult to extract the total lipid content of the cell as such. Thus, the cell disruption before lipid extraction becomes mandatory and has to be cost-effective. In the present study various methods and combination of few methods were adopted for effective extraction in order to choose the most effective cell disruption method for the complete extraction of lipids from a selected indigenous freshwater isolate, Scenedesmus sp. NTEB03. Interestingly, we found that grinding and bead-beating method showed two fold increased lipid productivity (23.2%) than the other methods tested. Biomass and lipid productivity of Scenedesmus sp., was found to be 0.0418 g L-1 d-1 and 4.3 mg L-1 d-1 respectively. Fatty acid profiles revealed that oleic (C18:1) and linoleic acid (C18:2) content being higher in the lipids, which are most appropriate for the biodiesel production. A novel strategy for most effective, simple method for cell disruption in Scenedesmus sp., was grinding/bead-beating, which is the most suitable method for complete extraction of biofuel grade lipids.